Comparative functional genomic screens of three yeast deletion collections reveal unexpected effects of genotype in response to diverse stress. Issue 6 (7th June 2017) - Acton, Erica; Lee, Amy Huei-Yi; Zhao, Pei Jun; Flibotte, Stephane; Neira, Mauricio; Sinha, Sunita; Chiang, Jennifer; Flaherty, Patrick; Nislow, Corey; Giaever, Guri
Abstract : Abstract : The Yeast Knockout (YKO) collection has provided a wealth of functional annotations from genome-wide screens. An unintended consequence is that 76% of gene annotations derive from one genotype. The nutritional auxotrophies in the YKO, in particular, have phenotypic consequences. To address this issue, 'prototrophic' versions of the YKO collection have been constructed, either by introducing a plasmid carrying wild-type copies of the auxotrophic markers (Plasmid-Borne, PBprot ) or by backcrossing (Backcrossed, BCprot ) to a wild-type strain. To systematically assess the impact of the auxotrophies, genome-wide fitness profiles of prototrophic and auxotrophic collections were compared across diverse drug and environmental conditions in 250 experiments. Our quantitative profiles uncovered broad impacts of genotype on phenotype for three deletion collections, and revealed genotypic and strain-construction-specific phenotypes. The PBprot collection exhibited fitness defects associated with plasmid maintenance, while BCprot fitness profiles were compromised due to strain loss from nutrient selection steps during strain construction. The repaired prototrophic versions of the YKO collection did not restore wild-type behaviour nor did they clarify gaps in gene annotation resulting from the auxotrophic background. To remove marker bias and expand the experimental scope of deletion libraries, construction of a bona fide prototrophic collection from a wild-type strain will be required.